Research On Structural Design and Performance Optimization of Diamond Transistors - Wang , Yaoli (Transactions on Computer Science and Intelligent Systems Research, 2024)
With the increasing demand for transistors that work in high-power, high-frequency, and high-voltage environments, diamond transistors are set to become an indispensable part of future transistor development. This article reviews the development history of hydrogen-terminated diamond transistors and silicon-terminated diamond transistors. Specifically, this article summarizes the invention of hydrogen-terminated and silicon-terminated diamond transistors, along with recent structural innovations and data analysis. From the recent findings on hydrogen-terminal diamond transistors, this paper finds that the structure of hydrogen-terminated diamond transistors is already mature. However, silicon-terminated diamond transistors are still in the development stage, and scientists are still looking for a new structure to make the output of silicon-terminated diamond transistors more stable and improve the efficiency of silicon-terminated diamond transistors. Last but not least, diamonds are also used to build FinFETs. Although there are few studies on this type of diamond transistor, significant progress has still been made in the development of diamond transistors.